2018
DOI: 10.1093/jxb/ery299
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of ZmNF-YA3 in photoperiod-dependent flowering and abiotic stress responses in maize

Abstract: Nuclear factor-Y (NF-Y) transcription factors are important regulators of several essential biological processes, including embryogenesis, drought resistance, meristem maintenance, and photoperiod-dependent flowering in Arabidopsis. However, the regulatory mechanisms of NF-Ys in maize (Zea mays) are not well understood yet. In this study, we identified an NF-Y transcription factor, ZmNF-YA3. Genome-wide analysis showed that ZmNF-YA3 bound to >6000 sites in the maize genome, 2259 of which are associated with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 51 publications
0
59
0
Order By: Relevance
“…In view of the partially redundant biological function in Arabidopsis and sequence diversity (mainly at the C-terminus) between ZmCCA1a and AtCCA1/ AtLHY, it would be intriguing to determine (1) the exact sequence in the C-terminus of ZmCCA1a that is responsible for the absence of homodimer or heterodimer formation, which is observed in AtCCA1 and AtLHY, and the biological meaning of the interactions; (2) how much of the ZmCCA1a function in Arabidopsis can be extended to maize, its native host; and (3) the stage at which the function of ZmCCA1a is regulated, given that AtCCA1 can be regulated both post-transcriptionally and posttranslationally, such as by alternative splicing and protein interaction and phosphorylation (Xavier et al, 2004;Esther et al, 2009;Seo et al, 2012). AtCCA1 is involved in the circadian regulation of temperature responses in Arabidopsis (Seo et al, 2012) and ZmCCA1a might play an important role in linking the photoperiod to stress tolerance responses (Su et al, 2018;Tian et al, 2019). Thus, it will be informative to determine the role of ZmCCA1a in stress tolerance responses and how photoperiod and stress tolerance responses are linked.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the partially redundant biological function in Arabidopsis and sequence diversity (mainly at the C-terminus) between ZmCCA1a and AtCCA1/ AtLHY, it would be intriguing to determine (1) the exact sequence in the C-terminus of ZmCCA1a that is responsible for the absence of homodimer or heterodimer formation, which is observed in AtCCA1 and AtLHY, and the biological meaning of the interactions; (2) how much of the ZmCCA1a function in Arabidopsis can be extended to maize, its native host; and (3) the stage at which the function of ZmCCA1a is regulated, given that AtCCA1 can be regulated both post-transcriptionally and posttranslationally, such as by alternative splicing and protein interaction and phosphorylation (Xavier et al, 2004;Esther et al, 2009;Seo et al, 2012). AtCCA1 is involved in the circadian regulation of temperature responses in Arabidopsis (Seo et al, 2012) and ZmCCA1a might play an important role in linking the photoperiod to stress tolerance responses (Su et al, 2018;Tian et al, 2019). Thus, it will be informative to determine the role of ZmCCA1a in stress tolerance responses and how photoperiod and stress tolerance responses are linked.…”
Section: Discussionmentioning
confidence: 99%
“…Although NF-Y transcription factors have been broadly studied in several plant species, such as Arabidopsis thaliana [41], Glycine max [42], Oryza sativa [43], Zea mays [29], Triticum aestivum [44],…”
Section: Discussionmentioning
confidence: 99%
“…In addition to plant growth and development, NF-Y participates in stress response and hormone signaling. According to the reports, we find studies on NF-Y mainly focus on drought resistance 4 [22][23][24], ABA response [18,22,25] and salt stress [23,26], a small part involving temperature [27], photoprotective [28,29]. In brief, as an important transcription factor in response to drought stress, NF-Y is mainly regulated by miR169, ABA crossing signal and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the zma-miR169s were up-regulated by external ABA and down-regulated by drought stress but showed an early increase in expression and later a decline in response to salinity stress. Recently, Su et al (2018) identified a NF-Y TF designated as ZmNF-YA3. Genome-wide analysis revealed that ZmNF-YA3 was linked to more than 6000 sites in the maize genome, 2259 of which are linked with genic sequences.…”
Section: Nf-y Transcription Factorsmentioning
confidence: 99%